PHD2 regulates arteriogenic macrophages through TIE2 signalling. Issue 6 (25th April 2013) - Hamm, Alexander; Veschini, Lorenzo; Takeda, Yukiji; Costa, Sandra; Delamarre, Estelle; Squadrito, Mario Leonardo; Henze, Anne‐Theres; Wenes, Mathias; Serneels, Jens; Pucci, Ferdinando; Roncal, Carmen; Anisimov, Andrey; et al.
Abstract Occlusion of the main arterial route redirects blood flow to the collateral circulation. We previously reported that macrophages genetically modified to express low levels of prolyl hydroxylase domain protein 2 (PHD2) display an arteriogenic phenotype, which promotes the formation of collateral vessels and protects the skeletal muscle from ischaemic necrosis. However, the molecular mechanisms underlying this process are unknown. Here, we demonstrate that femoral artery occlusion induces a switch in macrophage phenotype through angiopoietin‐1 (ANG1)‐mediated Phd2 repression. ANG blockade by a soluble trap prevented the downregulation of Phd2 expression in macrophages and their phenotypic switch, thus inhibiting collateral growth. ANG1‐dependent Phd2 repression initiated a feed‐forward loop mediated by the induction of the ANG receptor TIE2 in macrophages. Gene silencing and cell depletion strategies demonstrate that TIE2 induction in macrophages is required to promote their proarteriogenic functions, enabling collateral vessel formation following arterial obstruction. These results indicate an indispensable role for TIE2 in sustaining in situ programming of macrophages to a proarteriogenic, M2‐like phenotype, suggesting possible new venues for the treatment of ischaemic disorders. →See accompanying articles http://dx.doi.org/10.1002/emmm.201302752 and http://dx.doi.org/10.1002/emmm.201302794